Answer:
Solution of the equations is (1, -2).
Explanation:
Two linear equations given in the question are
y = -3x+1-------------(1)
and y = 2x-4 ------------(2)
To solve these equations by substitution method we will substitute the value of y from equation (1) to equation number (2).
-3x+1 = 2x-4
Now we add 3x on both the sides of the equation
3x-3x+1 = 3x+2x-4
1 = 5x-4
we will add 4 on both the sides
1+4 = 5x-4+4
5 = 5x
Then we divide the equation by 5
5/5 = 5x/5
x = 5/5 = 1
Now we solve the equation (1) for the value of y by putting x = 1
y = -3(1)+1 = -3+1 = (-2)
So the solution will be (1 -2).